Pengembangan Buku Penghubung Berbasis Android - Indriani, Ririn; Harjono, Hary Soedarto; Ali, Muhammad (JOEAI (Journal of Education and Instruction), 2021)
This study aims to explain how the feasibility, practicality, and development of an android-based link book application at SMAN 8 Tanjung Jabung Barat. This research is a type of R&D (Research & Development) research using the ADDIE development model which consists of 5 stages, consisting of analysis (analysis), design (design), development (development), implementation (implementation) and evaluation (evaluation). Data was collected by means of observation and interviews which were used to conduct needs analysis, while the questionnaire was used to obtain data on the feasibility of the product. The data analysis technique used descriptive statistical analysis to analyze quantitative data obtained from expert validation questionnaires and product trial questionnaires. To analyze the qualitative data, the technique of checking the validity of the data is triangulation of sources, triangulation of methods and triangulation of theory. Based on the results of data analysis, it is known that the display aspect gets an average rating score of 4.5 with a percentage of 90%. The ease of use aspect obtained an average score of 3.67 with a percentage of 73.33%. Then the linguistic aspect obtained an average score of 4 with a percentage of 80%. Furthermore, the implementation aspect obtained an average score of 4.33 with a percentage of 86.67%. Of the four aspects of the assessment, the highest score is in the display aspect with a percentage score of 90%. While the overall aspect of the assessment by media experts, obtained a score of 16.5 with a percentage of 82.50%, which is included in the very decent category. In conclusion, the android-based link book is very feasible and practical to use at SMAN 8 Tanjung Jabung Barat. This android-based link book can help make it easier for teachers to report student activities at school. Keywords: Android Application. Liaison Book, Development